Paraneoplastic pemphigus - Sang Eun Lee; Soo-Chan Kim (Dermatologica Sinica, 2010)
Paraneoplastic pemphigus (PNP) is a life-threatening autoimmune mucocutaneous blistering disease associated with malignancy, particularly lymphoproliferative neoplasms. Clinically, it is characterized by severe and intractable mucositis and polymorphous cutaneous eruptions, ranging from blisters to lichenoid lesions. The histologic features are also diverse according to the morphology of the clinical lesions, ranging from suprabasal acantholysis to interface changes with necrotic keratinocytes. PNP is characterized by the production of autoantibodies against the plakin family proteins as well as the desmoglein 1 and 3, which are target antigens of ordinary pemphigus. Thus, indirect immunofluorescence on substrates other than skin is useful in the diagnosis of PNP. The presence of anti-desmoglein antibodies have been demonstrated by enzyme-linked immunosorbent assay. The gold standard for the diagnosis of PNP however, is the detection of the characteristic circulating autoantibodies against 210-kDa envoplakin and 190-kDa periplakin by immunoblotting or immunoprecipitation. It is now accepted that both humoral and cellular immunities are involved in the pathogenesis of PNP. Anti-desmoglein 3 antibodies are known to play a pathogenic role in the initiation of acantholytic blister formation. Autoreactive CD8 + cytotoxic T cells induced by antitumor immune response are also involved in the development of mucocutaneous manifestations and bronchiolotis obliterans. The prognosis of PNP depends on the nature of the underlying neoplasm, with high mortality rate due to sepsis or multi-organ failure, particularly bronchiolitis obliterans. Although the combined use of immunosup-pressive agents and rituximab has been administered in treating PNP, to date, there are no consistently effective treatments for PNP.